Eksplorasi Kendala Administrasi Keimigrasian dalam Penerapan Kebijakan Visa dan Izin Tinggal di Indonesia - Daffa Raihan Arya Mas’adi (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
This study aims to explore immigration administrative constraints in the implementation of visa and residence permit policies in Indonesia which still face complex challenges in terms of regulation, bureaucracy, human resources, and technological infrastructure. Through a descriptive qualitative approach, this study collected primary data from in-depth interviews with immigration officials, visa applicants, and legal practitioners, as well as non-participant observations at immigration offices. Secondary data were obtained from laws and regulations, official reports, and academic literature. The results of the study show that immigration regulations often overlap with other sectoral rules, causing implementation inconsistencies and legal uncertainty. The convoluted and slow bureaucratic process also worsens the quality of public services, while the practice of illegal levies still occurs due to weak supervision. In addition, the limitation of information technology infrastructure causes digital services to not run evenly throughout the region. The capacity of human resources in the immigration sector is still not optimal, both in terms of technical competence and professionalism. The complexity of these problems has an impact on low public trust, declining investment competitiveness, and the emergence of negative perceptions of the performance of immigration institutions. This study recommends the need for comprehensive reform through regulatory harmonization, bureaucratic simplification, strengthening human resource capacity, and equitable use of digital technology. Thus, Indonesia's immigration policy is expected to be more responsive, transparent, and accountable in facing the challenges of globalization and international mobility.